PEST INCIDENCE-SEVERITY OF TENUPALPUS PACIFICUS TOWARDS LEAF MASS AREA (LMA) ON SEVERAL Dendrobium SPP. - Faozan Indresputra; Sri Rahayu; Suradi Suradi; Dedi Damhuri; Yuniar Yuniar (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2022)
Many of Dendrobium spp. are famous due to its beauty and medicinal uses. Their preserving efforts are still top priority among orchid plants in Bogor Botanical Garden (BBG). However, false spider mite (Tenupaipus pacificus) caused damages on leaves of several dendrobium species under greenhouse conditions. We examined diseases assessments of incidence-severity to the most visually attacked species such as Dendrobium bigibbum, Dendrobium lineale, Dendrobium sanguinolentum and Dendrobium secundum. We also measured Leaf Mass Area (LMA) as a defensive trait that might influence patterns of the pest’s attack. The assessment showed that D. secundum had the highest average incidence-severity (0.84 and 0.30 respectively) among other species. This pattern was correlated with its lowest average LMA (41.86 g m-2) compared to D. lineale which had the opposite patterns both LMA and incidence-severity. Positive correlation on incidence-severity with tendentiously lower severity than incidence suggest that T. pasificus was still in outbreak but it had not reached fatal damages or deadly result since two other species, D. bigibbum and D. lineale, had high LMA that could slow the feeding rate of pest’s behavior. This result is expected to be basic sanitary control management to overcome the pests.